2002
DOI: 10.1021/om0204991
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionation of PtPh(CH2COMe)(cod) and Conproportionation of PtPh2(cod) and Pt(CH2COMe)2(cod) via Intermolecular Phenyl Ligand Transfer

Abstract: PtI(Ph)(cod) (cod ) 1,5-cyclooctadiene) reacts with acetone in the presence of Ag 2 O to give a mixture of Pt(CH 2 COMe)(Ph)(cod) (1), PtPh 2 (cod) (2), and Pt(CH 2 COMe) 2 (cod) (3) in a molar ratio of 61:20:19. Complex 1, having the phenyl and acetonyl ligands, was isolated by recrystallization of the products and characterized by X-ray crystallography. The reaction of AgBF 4 with PtI(Ph)(cod) forms [PtPh(cod)(acetone-d 6 )]BF 4 and does not give a diarylplatinum complex. Thus, Ag 2 O, in the reaction of PtI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
(15 reference statements)
4
25
0
Order By: Relevance
“…Ligand disproportionation of a Pt complex with aryl and acetonyl ligands has been reported by Osakada et al to give diaryl-platinum and diacetonyl-platinum complexes, both in acetone and in benzene. [46] Recently, Sanford and co-workers studied, computational and experimentally, the influence of ancillary ligands on the ligand disproportionation of cis- L 2 ] intermediates, which eventually leads to undesired homocoupling products in the cross-coupling reactions (Scheme 21). [48][49][50] Lo Sterzo et al have reported a number of examples of palladium-catalyzed metal-carbon bond-formation with alkynyl stannanes (Scheme 22), [51][52][53][54] and have detected spectroscopically a pentacoordinated palladium intermediate that is suggested to be a model of the transition state proposed in the cyclic mechanism of the Stille reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Ligand disproportionation of a Pt complex with aryl and acetonyl ligands has been reported by Osakada et al to give diaryl-platinum and diacetonyl-platinum complexes, both in acetone and in benzene. [46] Recently, Sanford and co-workers studied, computational and experimentally, the influence of ancillary ligands on the ligand disproportionation of cis- L 2 ] intermediates, which eventually leads to undesired homocoupling products in the cross-coupling reactions (Scheme 21). [48][49][50] Lo Sterzo et al have reported a number of examples of palladium-catalyzed metal-carbon bond-formation with alkynyl stannanes (Scheme 22), [51][52][53][54] and have detected spectroscopically a pentacoordinated palladium intermediate that is suggested to be a model of the transition state proposed in the cyclic mechanism of the Stille reaction.…”
Section: Introductionmentioning
confidence: 99%
“…3 Most reported acetonyl complexes [Pt(II)]CH 2 C(O)Me have been obtained through methods that inevitably lead to species also containing phosphines, pyridine derivatives, Me or Ph ligands. 4,5 The only acetonyl platinum complex containing an easily exchangeable ligand is [Pt{CH 2 C(O)Me} 2 (COD)] (COD 5 1,5-cyclooctadiene), which has recently been reported in low yield. 5 We have reported the synthesis of [Pd{CH 2 C(O)Me}Cl] n , which allows preparation of acetonyl palladium complexes choosing freely any additional ligand.…”
mentioning
confidence: 99%
“…4,5 The only acetonyl platinum complex containing an easily exchangeable ligand is [Pt{CH 2 C(O)Me} 2 (COD)] (COD 5 1,5-cyclooctadiene), which has recently been reported in low yield. 5 We have reported the synthesis of [Pd{CH 2 C(O)Me}Cl] n , which allows preparation of acetonyl palladium complexes choosing freely any additional ligand. 2 The same method that uses [Hg{CH 2 C(O)Me} 2 ] to transmetallate the acetonyl ligand, is here reported to give Pt(II) and Pt(IV) acetonyl chlorocomplexes.…”
mentioning
confidence: 99%
“…Carboxylic acids react with [Pt(CH 2 COMe)(Ph)(cod)] ( 1 ; cod=1,5‐cyclooctadiene) to form carboxylate–platinum complexes 23. This reaction is employed as the end‐capping reaction of pseudorotaxanes whose axis molecule has a carboxy group as the terminal group.…”
Section: Resultsmentioning
confidence: 99%
“…1 ,23 [Pt(X)(Ph)(cod)] (X=Cl, I, Ph),34 {(DB24C8)( 2 ‐H)} + (PF 6 ) − ,24 (ArCH 2 NH 2 CH 2 Ar) + (PF 6 ) − (( 7 ‐H) + (PF 6 ) − : Ar=Ph, ( 12 ‐H) + (PF 6 ) − : Ar=4‐ t BuC 6 H 4 ),25, 26 and (py‐H) + (PF 6 ) −[35] were prepared according to the methods in the literature. Other chemicals were commercially available.…”
Section: Methodsmentioning
confidence: 99%